2007
DOI: 10.3201/eid1310.070337
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Infection among Children, Bangladesh

Abstract: We confirmed circulation of human metapneumovirus (HMPV) among children with febrile and respiratory illness in an urban slum in Dhaka, Bangladesh, during active surveillance in 2001. HMPV was the most common single virus identified among febrile children and appears to contribute to the high rates of illness in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 12 publications
1
20
3
Order By: Relevance
“…Several studies have demonstrated that human metapneumovirus is more likely to be associated with bronchiolitis in early childhood [Xepapadaki et al, 2004;Garcia-Garcia et al, 2007;do Carmo Debur et al, 2007]. However, other investigations including the present study found that human metapneumovirus was associated more frequently with bronchopneumonia compared to human metapneumovirus-bronchiolitis cases [Choi et al, 2006;Brooks et al, 2007]. These variable results may reflect that human metapneumovirus is not exclusively a bronchiolitis pathogen and can, also cause bronchopneumonia among infants.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Several studies have demonstrated that human metapneumovirus is more likely to be associated with bronchiolitis in early childhood [Xepapadaki et al, 2004;Garcia-Garcia et al, 2007;do Carmo Debur et al, 2007]. However, other investigations including the present study found that human metapneumovirus was associated more frequently with bronchopneumonia compared to human metapneumovirus-bronchiolitis cases [Choi et al, 2006;Brooks et al, 2007]. These variable results may reflect that human metapneumovirus is not exclusively a bronchiolitis pathogen and can, also cause bronchopneumonia among infants.…”
Section: Discussioncontrasting
confidence: 55%
“…Human metapneumovirus was discovered recently as a respiratory virus implicated in both upper and lower respiratory tract infection ranging from mild to severe disease in all age groups [van den Hoogen et al, 2001]. Since then, it has been reported in Europe, Asia, Australia, South Africa and America [Peret et al, 2002;Bastien et al, 2003;Jpma et al, 2004;Rao et al, 2004;Sloots et al, 2006;Brooks et al, 2007], suggesting worldwide distribution. Seroprevalence studies have shown that this virus has been present among humans for over five decades [van den Hoogen et al, 2001;Hamelin et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…To test retrospectively for viral infection, serological assays can be performed using acute-and convalescentstage patient serum samples. For hMPV, tests have included immunofluorescence assays using hMPVinfected cells [11,15] or recombinant baculovirus-infected cells expressing the fusion (F) protein [16] as well as ELISAs using hMPV-infected cell lysates [17,18], lysates from recombinant baculovirus-infected cells expressing nucleoprotein [19], purified nucleoprotein from a prokaryotic expression system [20], and a recombinant vesicular stomatitis virus expressing hMPV F protein [6]. However, to our knowledge, no serological studies have been conducted using purified hMPV glycoproteins from a eukaryotic or human cell line system.…”
mentioning
confidence: 99%
“…Most hMPV infections occur within the first few years of life, usually later than those for hRSV, and cause 5 to 10% of respiratory infections in children requiring hospitalization, second only to hRSV (7). Both viruses are ubiquitous globally, and recent studies have documented a high prevalence of infection among children in less developed countries (8,9). Clinical outcomes similar to those for hRSV have been described for hMPV infections in the frail elderly (10).…”
mentioning
confidence: 74%
“…As part of a population-based respiratory disease surveillance study in Dhaka, Bangladesh, conducted by the International Center for Diarrheal Disease Research, Bangladesh (ICDDR, B), paired acute-and convalescent-phase serum specimens were collected from children Ïœ5 years of age presenting with acute respiratory tract illness and/or fever from April 2004 to Feb 2006. Serum pairs obtained from 852 children were sent to the Centers for Disease Control and Prevention (CDC; Atlanta, Georgia, USA) for serologic testing for respiratory pathogens (8). This study was reviewed and approved by the Research Review and Ethical Review Committees of ICDDR, B and the CDC Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%